Systemic adjuvant therapy for adult patients at high risk for recurrent melanoma: A systematic review. (July 2020) - Baetz, Tara D.; Fletcher, Glenn G.; Knight, Gregory; McWhirter, Elaine; Rajagopal, Sudha; Song, Xinni; Petrella, Teresa M.
Highlights: Adjuvant pembrolizumab or nivolumab are effective in cutaneous melanoma. Ipilimumab is also effective but adverse events are more frequent and severe. For BRAF v600E/K mutations, dabrafenib plus trametinib also improved survival. Interferon improved survival; benefit is small (3–6%) and it is no longer recommended. Evidence is insufficient for routine use of adjuvant chemotherapy or vaccines. Abstract: Cutaneous melanoma is typically treated with wide local excision and, when appropriate, a sentinel node biopsy. Many patients are cured with this approach but for patients who have cancers with high risk features there is a significant risk of local and distant relapse and death. Interferon-based adjuvant therapy was recommended in the past but had modest results with significant toxicity. Recently, new therapies (immune checkpoint inhibitors and targeted therapies) have been found to be effective in the treatment of patients with metastatic melanoma and many of these therapies have been evaluated and found to be effective in the adjuvant treatment of high risk patients with melanoma. This systematic review of adjuvant therapies for cutaneous and mucosal melanoma was conducted for Ontario Health (Cancer Care Ontario) as the basis of a clinical practice guideline to address the question of whether patients with completely resected melanoma should be considered for adjuvant systemic therapy and which adjuvant therapy should be used.